Modelling the plastic deformation of iron - Chen, Zhiming (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2013)
The 1/2<111> screw dislocations in bcc iron are studied by atomistic simulations. An analytical yield criterion captures correctly the non-Schmid plastic behavior. A model Peierls potential develops a link between the atomistic modeling at 0 K and the thermally activated dislocation motion. All predicted features agree well with experimental observations. This work establishes a consistent bottom-up model that provides an insight into the microscopic origins of the plastic behavior of bcc iron.